Towards a definition of Zeus-Light: notes on Hesiodus (Minerva, 2019)
Starting from the relevant passages of the Theogony by Hesiod, the author has tried to point out the close relation between Zeus and the light, considered both in physical and spiritual sense, as some of the divinities that originated from Zeus-light seem to demonstrate. Looking through the differences as regards the fire and the lightning –Zeus’ specific attribute–, you might recognize, in this property of the lord of gods, a kind of fifth primeval element, besides air, water, earth and fire.
Keywords: Hesiod; Theogony; Zeus-light; primeval elements